E-COMMERCE IMPLEMENTATION IN CAKE STORE MBA WATI IN SUKARAJA 2 GEDONGTATAAN - Nova Puspitasari (IJISCS (International Journal of Information System and Computer Science), 2018)
KueMbaWati is a small business that is engaged in selling cakes at this time. The sales system in the Cake Shop MbaWati in sales and purchases is still manual or the customer comes directly to the location. Meanwhile, in promoting its products to customers, KueMbaWati still uses brochures. Such a promotion system is felt to be less than optimal, due to the lack of information provided regarding the product details offered. The development of E-Commerce Applications in the MbaWati Cake Shop is a step to increase sales and facilitate product promotion, so that it can provide benefits for business owners. With this E-Commerce application, customers can order products online. E-Commerce at the MbaWati Cake Shop designed using modeling with the SDLC method (Systems Development Life Cycle) is expected to increase sales and facilitate the making of its implementation.E-Commerce, MbaWati Cake Sho